Effect of Berberine on C-reactive protein: A systematic review and meta-analysis of randomized controlled trials. (October 2019) - Beba, Mohammad; Djafarian, Kurosh; Shab-Bidar, Sakineh
Highlights: Effect of Berberine (BER) on serum C- reactive protein is inconclusive. Pooled analysis showed that serum levels of CRP were decreased after BER supplementation by 0.64 mg/L. Further well-designed investigations with larger samples are needed to confirm this finding. Abstract: Objectives: Clinical evidence suggests the beneficial effects of Berberine (BER) on inflammatory markers. However, these results are controversial. The aim of this systematic review was to assess the effects of BER on C-reactive protein (CRP) using clinical trials in adults. Design: Systematic review and meta-analysis. Main outcome measures: We searched randomized controlled trials in PubMed and Scopus up to November 2018. The mean differences (MD) and confidence interval (CI) of CRP (mg/L) concentrations were pooled with a random- or a fixed-effects model depending on the results of heterogeneity tests. Results: Of 1242 studies identified, 5 were included in the meta-analysis. Pooled analysis showed that serum levels of CRP were decreased after BER supplementation (MD:-0.64 mg/L, 95% CI(-0.67 to -0.61) P < 0.001)) without any significant heterogeneity (I 2  = 0.0% and P = 0.984). Conclusion: This meta-analysis showed BER supplementation may ameliorate the state of chronic inflammation. Patients with cardiovascular disease and diabetes are two important groups which may benefit from BER supplementation. Further well-designed investigations with larger samples are needed to ascertain the long-term effects of BER on chronic inflammation.